The Strategy of Budget Disbursement Optimization in The Agency of Public Works and Spatial Planning of Bogor Regency - Rizkia, Tatu; Hakim, Dedi Budiman; Falatehan, A Faroby (JURNAL MANAJEMEN AGRIBISNIS, 2020)
The research is conducted according to budget realization report of Public Works and Spatial Planning Office (DPUPR) of Bogor Regency. DPUPR of Bogor Regency is one of Local Government Working Unit (SKPD) that get the lowest percentage of budget realization among others SKPD around Bogor Regency. This research aimed to find out the main cause of lack of direct expense disburesement and to formulate the strategy to optimize the disbursement of direct expense at DPUPR of Bogor Regency. By using likert scale analysis, it can be determined the main cause of lack of direct expense disburesement at DPUPR of Bogor Regency.The result indicate the main cause of lack of direct expense disburesement at DPUPR of Bogor Regency is that the good and service provider (partner) submit the disbursement at once in the end of year. Based on AHP (Analitycal Hierarchy Process) method, the strategy choosen to optimize the disbursement of direct expense at DPUPR of Bogor Regency is that making strict regulation for the good and service provider (partner) in order to good administration (Regency Regulation/Regent Regulation).